Are diatom types or patterns in the organs and water samples of drowning cases always consistent?. Issue 3 (4th May 2022) - Li, Huan; Kang, Xiaodong; Zheng, Dongyun; Zhang, Pingping; Xiao, Cheng; Yu, Zhonghao; Shi, He; Xu, Quyi; Zhao, Jian; Liu, Chao; Wan, Lihua
ABSTRACT: Diatoms detected in the organs of corpses are considered reliable indicators for the diagnosis of drowning. However, this remains a disputed area regarding the consistency of diatom types and patterns in the organs and drowning medium. In this study, 93 cases (30 cases with known drowning sites, 63 cases with drowning sites undetermined) were the subjects for the diatom test. Samples from the victims (liver, kidney, lung and water samples) and drowning medium samples were analysed by the Microwave Digestion – Vacuum Filtration – Automated Scanning Electron Microscopy method (MD-VF-Auto SEM method). Two methods – type consistency and cluster analysis – were used to analyse the diatom types and patterns in different organs and water samples for evaluating the diatom consistency in drowning cases. The results showed that the inconsistent proportion is about 40% in the drowning-site-determined cases, and the lowest consistent proportion is 40% in the drowning-site-undetermined cases. In conclusion, consistency of diatoms in the organs and water samples would not be a necessary requirement for the diagnosis of drowning, but it has potential value for inferring the site of drowning.